Legal Politics of Protection and Ownership of Communal Intellectual Property: A Study of Traditional Medicine Knowledge - Zainul Daulay (Warmadewa Press, 2022)
The protection of cultural property can have two meanings. It depends on the perspective of whether the cultural wealth is seen as a cultural heritage or resource. In the event that cultural wealth is a cultural heritage, protection means preservation. The rsults shown that all KIK is a common heritage is based on generalizations and is a misguided conclusion rather than an accurate fact. It is recognized that many traditional communities have a strong and high ethos of sharing and giving (a strong sharing ethos). Although some KIK, knowledge of traditional medicine, for example, has been opened and disclosed, this knowledge is protected by customary law practices which view traditional knowledge as knowledge that cannot be accessed and used freely by everyone. This is in accordance with the theory of ownership where private property is in the middle between the commons and the anticommons. Therefore, the holder of the right to private property can be the state, the community collective and individuals. The legal politics of protection and ownership of communal intellectual property must reflect and rely on Pancasila as the basis of the state, constitution and sociological facts in indigenous peoples. There must be a balance between individual interests and the interests of the common or communal groups of owners of traditional knowledge. The regulation of KIK should be specifically regulated (sui generis) in a complete statutory regulation by taking into account the ideal policy of protecting the ownership of Indigenous Peoples.